The Galician republicanism: The Suarez Picallo’s Chronicles - Manríquez Bergenfreid, Constanza; Suárez González, Andrés (Madrygal. Revista de Estudios Gallegos, 2012)
This article examines the figure of the galician intelectual Ramón Suárez Picallo (1894-1964) and some of the chronicles that he wrote in Chile between 1942 and 1956 and that were compiled in the book La feria del mundo (2008). One of his motivations for having written the chronicles may have been his republican exile in America, especially his galician exile. Suárez Picallo points to Chile and to other Latin American countries as a political example for Spanish republicanism.
Keywords: La feria del mundo; Ramón Suárez Picallo; Galician exile; Spanish republicanism.